### Poll Results

Please login to vote and see the results.

Lost your password? Please enter your email address to get a reset link.

Please briefly explain why you feel this question should be reported.

Please briefly explain why you feel this answer should be reported.

Please briefly explain why you feel this user should be reported.

Correct Answer: x=p2−q2/mp−nq,y=p2−q2/np−mq

p/x+q/y=m …(i)

q/x+p/y=n …(ii)

On multiplying Eq. (i) by q and Eq. (ii) by p and subtracting, we get

pq/x+q2/y=mq

pq/x+p2/y=np

q2/y−p2/y=mq−np

Therefore, q2−p2=y(mq−np)

Therefore, y=q2−p2/mq−np=p2−q2/np−mq

Again, on multiplying Eq. (i) by p and Eq. (ii) by q and subtracting, we get

p2/x+pq/y=m/p

q2/x+pq/y=n/q

p2x−q2x=mp−nq

= p2−q2=x(mp−nq)

= x=p2−q2/mp−nq

Therefore, x=p2−q2/mp−nq

and y=p2−q2/np−mq